Systematic review of the cost-effectiveness of insulin in the treatment of type 2 diabetes - Nhi, Vo Ngoc Yen; Son, Pham Luong; Dung, Nguyen Tan; Thuy, Nguyen Thi Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a major chronic disease requiring lifelong treatment. Insulin therapies play a key role in glycemic control, but their cost-effectiveness varies widely across formulations and delivery methods. Objectives: Systematic review of the cost-effectiveness of insulin in the treatment of type 2 diabetes. Materials and methods: A systematic review (SR) following PRISMA guidelines searched PubMed, Cochrane, Embase, and Vietnamese journals up to December 4, 2024. Eligible studies met predefined criteria and were appraised using the CHEERS 2022 checklist. Cost data and ICERs were converted to 2024 USD for comparison. Results: From 7,873 records, 84 studies were included (3 on delivery forms, 5 on injection methods, and 76 on insulin molecules). Thirteen recent studies (2020 onward) were analyzed for comparisons between insulin molecules; most (12/13) used model-based analysis and were high-quality. Insulin degludec was cost-effective or dominant compared with other basal insulins; icodec saved 480 - 974 USD and gained 0.04 - 0.08 QALYs compared with degludec. Glargine 100 was cost-effective compared with NPH (ICER 424 - 21,590 USD) and dominant over detemir. Pen devices improved adherence and glycemic control despite higher costs; insulin pumps were more cost-effective than multiple daily injections (ICER 64,433 - 104,069 USD/QALY). Stepwise initiation saved 3,370 USD and added 0.08 QALYs. Conclusions: The SR confirmed the cost-effectiveness of new insulin therapies and provides valuable evidence for future pharmacoeconomic evaluations.